Darurat Sampah Plastik: Resistensi Masyarakat terhadap Kebijakan Penanggulangan Sampah Plastik di Kota Denpasar - Ibnu Hajar (Jurnal Riset Rumpun Seni, Desain dan Media, 2025)
The plastic waste emergency in Denpasar reflects an ecological and social crisis due to the accumulation of single-use plastics. In response, the Bali Provincial Government issued Governor Regulation No. 97/2018, though its implementation remains limited. This study analyzes forms of community resistance to the policy and identifies structural causes and implications. Using a qualitative approach grounded in Cultural Studies, the research reveals resistance in passive, symbolic, and active forms, driven by information asymmetry, economic burdens, and lack of participatory policy-making. Findings show resistance as an articulation of agency within power/knowledge relations. The study concludes that environmental policy success depends on authentic public engagement as subjects of change.